Inflammatory pseudotumor of the spleen - Čolović Nataša; Čolović Radoje; Grubor Nikica; Micev Marijan; Radak Vladimir; Stojković Mirjana (Vojnosanitetski Pregled)
Background. Inflammatory pseudotumors are benign tumor lesions of an unknown etiology that can appear almost at any organ, sometimes along with infectious agens, like Epstein-Barr virus. They are extremely rare in the spleen, with less than 80 cases described in the world literature. It is a single, very rarely multinodal lesion. Middle aged patients are mostly affected. Symptoms are either absent or uncharacteristic, so that the tumors are discovered by chance or during investigations of other diseases. Case report. We presented a 56-year-old woman in whom a nodal lesion of 2 cm in diameter had been discovered in the spleen during a routine check-up after a mild traffic accident. The lesion had grown up to 6 cm in diameter during a 5-year follow-up causing a mild pain over the upper left abdomen and left shoulder. Fine needle biopsy failed to show the exact nature of the lesion. Splenectomy was performed due to a suspected lymphoproliferative disorder. Histology and immunohistochemistry of the lesion of the upper pole of the spleen showed inflammatory pseudotumor. Epstein-Barr virus was not present. The patient developed postsplenectomy thrombocytosis (up to 850 × 109/l) which settled down within 10 weeks. Conclusion. Inflammatory pseudotumors of the spleen are extremely rare. The exact diagnosis can be established only by histology and/or immunohistochemistry of the spleen removed for a suspected lymphoproliferative disorder, most frequently lymphoma. The patient was cured with splenectomy.